Teknologi dan sumber bahan gerabah Situs Mulyosari berdasarkan analisis petrografi - Putri Novita Taniardi; Anggara Nandiwardhana; Maulana Ainul Yaqin; Citra Iqliyah Darojah (Balai Arkeologi Yogyakarta, 2021)
Since the research in 2018 until 2019, pottery sherds are the most dominant artifact from Mulyosari megalithic site amongst other. Hence, analysis conducted towards pottery directly associated with the megaliths are important. Petrographic analysis that was applied in this research is aiming to understand the technology and the material source of pottery at Mulyosari Site. It is necessary to know whether the pottery is locally made or imported from other region. Petrographic analysis was carried out to several excavated pottery samples. All the samples were not randomly chosen; instead they were based on specific character of pottery sherds. The result of analysis shows that the source of pottery material located within geological formation of researched area comprises Sukamade, Merubetiri, Batu Ampar, and Merubetiri limestone. The result of analysis also shows advanced pottery making technology using spinning wheel and open firing at 400 Celsius degrees.